2015
DOI: 10.3386/w20828
|View full text |Cite
|
Sign up to set email alerts
|

The Fluidity of Race: “Passing” in the United States, 1880-1940

Abstract: This paper quantifies the extent to which individuals experience changes in reported racial identity in the historical U.S. context. Using the full population of historical Censuses for 1880-1940, we document that over 19% of black males "passed" for white at some point during their lifetime, around 10% of whom later "reverse-passed" to being black; passing was accompanied by geographic relocation to communities with a higher percentage of whites and occurred the most in Northern states. The evidence suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 47 publications
0
30
1
Order By: Relevance
“…At the same time, research indicates that minorities do exercise their option of assimilating to avoid discrimination. "Passing" for white was a strategy for improving one's economic situation that was sometimes employed among blacks in the US during the Jim Crow era (Mill and Stein 2016;Nix and Qian 2015;Saperstein and Penner 2012). Immigrants during the era of mass migration Americanized their names and in so doing achieved better labor market outcomes, a fact that implies that there was a penalty on foreign-sounding names (Biavaschi, Giulietti, and Siddique 2017).…”
Section: Discrimination and Assimilationmentioning
confidence: 99%
“…At the same time, research indicates that minorities do exercise their option of assimilating to avoid discrimination. "Passing" for white was a strategy for improving one's economic situation that was sometimes employed among blacks in the US during the Jim Crow era (Mill and Stein 2016;Nix and Qian 2015;Saperstein and Penner 2012). Immigrants during the era of mass migration Americanized their names and in so doing achieved better labor market outcomes, a fact that implies that there was a penalty on foreign-sounding names (Biavaschi, Giulietti, and Siddique 2017).…”
Section: Discrimination and Assimilationmentioning
confidence: 99%
“…Something similar occurred in the USA. Nix & Qian (2015) report that 20% of black men "passed" as whites during the 1880-1960 period, probably motivated by better social, political and economic opportunities. Antman & Duncan (2015) present evidence from more recent years (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011).…”
Section: Racial Aspects In Brazilmentioning
confidence: 99%
“…For causal inference it is critical that each household be potentially exposable to any of the causes (Holland, 1986) and race or ethnicity is not a choice or a manipulable action in general. Nix and Qian (2015) find that race change in US was a widespread phenomenon between 1880 and 1940, responding to strong social, economic and political incentives for Blacks to "pass" for Whites. Liebler et al (2014) note that the measure of the ethnic savings gap based on self-reported ethnicity rather than on the birthplace of the individual and his ancestors may be overestimated if the better off, higher-generation Hispanics do no self-identify as such (Duncan and Trejo, 2011).…”
Section: Empirical Applicationmentioning
confidence: 97%